High resolution clonal architecture of hypomutated Wilms tumours - Henry Lee-Six; Taryn D. Treger; Manas Dave; Tim HH Coorens; Nathaniel D. Anderson; Yvonne Tiersma; Sepide Derakhshan; Sanne de Haan; Marry M. van den Heuvel-Eibrink; Yichen Wang; Anna Wenger; Reem Al-Saadi; et al. (Nature Communications)
Abstract A paradigm of childhood cancers is that they have a low mutation burden, with some ostensibly bearing fewer mutations than the normal tissues from which they derive. We set out to resolve this paradox by examining paediatric renal cancers with exceptionally few mutations using high resolution, high depth sequencing approaches. We find that apparent hypomutation is the result of unusual clonal architecture due to a normal tissue-like mode of tumour evolution, raising the possibility that the mutation burden of some cancers has been systematically misjudged.